2017
DOI: 10.1155/2017/4719279
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thyroid Hormone Levels on Functional Outcome in Neurological and Neurosurgical Early Rehabilitation Patients

Abstract: Background Neurological and neurosurgical early rehabilitation (NNER) is a specialized treatment option for patients with severe neurological disorders. The present study investigated whether thyroid hormone levels on admission have an impact on the outcome of NNER patients. Method The study included 500 NNER patients who were admitted to the BDH-Clinic Hessisch Oldendorf between 2009 and 2010. Data such as age, sex, diagnoses, comorbidities, Glasgow Coma Scale score, length of stay, and thyroid hormone levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
9
1
1
Order By: Relevance
“…While TSH proved to be a relevant outcome predictor in univariate and multivariate analyses in the present study, the fT3 level was not found to be an independent predictor of outcome. This finding contrasts with a previous study investigating thyroid hormone levels in a sample of early neurological rehabilitation patients [ 35 ]. Here, decreased total T3 levels independently predicted an unfavorable functional outcome at the end of early rehabilitative treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…While TSH proved to be a relevant outcome predictor in univariate and multivariate analyses in the present study, the fT3 level was not found to be an independent predictor of outcome. This finding contrasts with a previous study investigating thyroid hormone levels in a sample of early neurological rehabilitation patients [ 35 ]. Here, decreased total T3 levels independently predicted an unfavorable functional outcome at the end of early rehabilitative treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…In neurological rehabilitation outcome studies, age is an important and independent prognostic factor (e.g., in stroke [ 33 ]). For phase B treatment, age has been shown to predict both functional status at discharge [ 23 , 34 ] and discharge disposition [ 23 ]. In contrast to previous studies, the cause of brain damage was not related to outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, however, functional status will be investigated because it is an important outcome measure in neurological early rehabilitation. The functional status at the end of early rehabilitation, measured with the Early Rehabilitation Barthel Index (ERBI), has been shown to be associated with functional status upon admission, CRS-R score upon admission, age, and time since injury [ 23 , 24 ]. The objective of the present study is to identify the influence of different clinical variables collected during the first four weeks on the functional status at the end of rehabilitative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies suggests that thyroid status may influence recovery, prognosis, and outcomes of rehabilitation in stroke patients, but published data provide partially inconsistent results [8][9][10][11][12]. Therefore, the complex interrelationships between the thyroid, the heart and the brain remain an area of interest with a potential for future prevention and treatment approaches.…”
Section: Introductionmentioning
confidence: 99%